2022
DOI: 10.1186/s12864-022-08786-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome‑wide identification, phylogenetic and expression pattern analysis of GATA family genes in foxtail millet (Setaria italica)

Abstract: Background Transcription factors (TFs) play important roles in plants. Among the major TFs, GATA plays a crucial role in plant development, growth, and stress responses. However, there have been few studies on the GATA gene family in foxtail millet (Setaria italica). The release of the foxtail millet reference genome presents an opportunity for the genome-wide characterization of these GATA genes. Results In this study, we identified 28 GATA genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
3
14
1
Order By: Relevance
“…The pI of 16/28 (57.14%) FtGATA genes was under seven ( Table S2 ), indicating that most FtGATA genes were rich in acidic amino acids. However, this was contrary to the results of some GATA transcription factors [ 35 , 37 , 38 ], and the findings for different protein families in Tartary buckwheat were consistent [ 39 ]. This indicated that the pI of the same gene family is different for different species, and the pI of the same species may be the same for different gene families.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The pI of 16/28 (57.14%) FtGATA genes was under seven ( Table S2 ), indicating that most FtGATA genes were rich in acidic amino acids. However, this was contrary to the results of some GATA transcription factors [ 35 , 37 , 38 ], and the findings for different protein families in Tartary buckwheat were consistent [ 39 ]. This indicated that the pI of the same gene family is different for different species, and the pI of the same species may be the same for different gene families.…”
Section: Discussioncontrasting
confidence: 69%
“…The tissues were rapidly placed in liquid nitrogen and stored at −80 °C [ 2 , 44 ]. In addition, the root, stem, young leaf, mature leaf, flower, fruit, and husk were taken from growing Tartary buckwheat to the grain-filling period; the fruits and husks were taken during the early, middle, and late grain-filling periods, and the samples were stored at −80 °C [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GATA gene family has been reported in many different plants. For example, previous reports revealed 30 GATA family members in Arabidopsis thaliana ( Reyes et al., 2004 ; Bi et al., 2005 ), 28 in rice ( Reyes et al., 2004 ; Gupta et al., 2017 ), 28 in foxtail millet ( Lai et al., 2022 ), 64 in soybean ( Zhang et al., 2015 ), and 79 in wheat ( Feng et al., 2022 ). However, primarily because commonly cultivated potato varieties are autotetraploids with highly heterozygous genomes, complicated genetic analysis and relatively scarce gene databases, the genome-wide investigation of the GATA gene family has not been performed in tetraploid potato.…”
Section: Discussionmentioning
confidence: 99%
“…The GATA transcription factor family is actively involved in light response and abiotic stress mechanisms, exhibiting high conservation across eukaryotes. Identified by a characteristic type IV zinc finger domain (CX 2 CX 17‐20 CX 2 C, where C represents cysteine and X is any amino acid) and a nearby basic region, GATA factors were first identified in tobacco (Daniel‐Vedele & Caboche, 1993 ) and have been extensively studied in various plant species, Arabidopsis thaliana (Kim, Xi, & Park, 2021 ; Teakle & Gilmartin, 1998 ), rice (Reyes et al, 2004 ), poplar (An et al, 2014 ), Noccaea caerulescens (Milner et al, 2014 ), soybean (Zhang et al, 2015 ), apple (Chen et al, 2017 ), grape (Zhang et al, 2018 ), Moso bamboo (Wang et al, 2019 ), Brachypodium distachyon (Peng et al, 2021 ), poplar (Kim, Xi, Park, Yun, & Park, 2021 ), cucumber (Zhang et al, 2021 ), potato (Yu, Chang, et al, 2021 ), wheat (Du et al, 2022 ; Feng et al, 2022 ), and foxtail millet (Lai et al, 2022 ). The GATA transcription factor‐binding cis ‐elements are commonly found in the promoters of genes associated with light and circadian rhythms, which are crucial for plant growth and development (Argüello‐Astorga & Herrera‐Estrella, 1998 ; Manfield et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%